Coaches' interpersonal style, basic psychological needs and the well- and ill-being of young soccer players: A longitudinal analysis - Balaguer, I.; González, L.; Fabra, P.; Castillo, I.; Mercé, J.; Duda, J. L. (Journal of Sports Sciences, 2012)
Abstract This study entailed a longitudinal test of basic psychological needs theory, a sub-theory in the self-determination framework (Deci n(T2)=597]. Changes in the players' perceptions of an autonomy supportive environment significantly predicted changes in psychological need satisfaction (positively) and in psychological need thwarting (negatively). Changes in psychological need satisfaction positively predicted changes in subjective vitality and negatively related to cross-time variation in global burnout scores. In contrast, changes in the players' perceptions of a controlling coach-created environment were positively associated with changes in psychological need thwarting that corresponded to increases in player burnout. Finally, results provided support for the assumed mediational roles of psychological need satisfaction and need thwarting in the social environment to well- and ill-being relationships.